Mitochondrial phosphate carrier plays an important role in virulence of Candida albicans - Qiao-Ling Hu; Hua Zhong; Xin-Rong Wang; Lei Han; Shan-Shan Ma; Ling Li; Yan Wang (Mycology)
Candida albicans is a common fungal pathogen that can cause life-threatening infections. MIR1 is considered to be a mitochondrial phosphate carrier of C. albicans, while its role in virulence has not been fully elucidated. In this study, we found that mir1Δ/Δ mutant exhibited severe virulence defect in both nematode and murine models. Further mechanism studies revealed that the mir1Δ/Δ mutant grew more slowly than the wild-type strain and showed severe filamentation defects on the hypha-inducing agar media, including YPD + serum, Lee, Spider + glucose, SLAD, SLD, and YPS. Furthermore, the loss of MIR1 resulted in unfermentable carbon utilisation defect, ATP decrease, and reactive oxygen species (ROS) accumulation in C. albicans. Antioxidant proanthocyanidins, vitamin E, and N-acetyl cysteine (NAC) could reduce intracellular ROS levels and partially rescue the filamentation defects of the mir1Δ/Δ mutant. Accordingly, hypha-specific genes, as well as CEK1 and RIM101 were down-regulated in the mir1Δ/Δ mutant, and this down-regulation could be partially rescued by the addition of the antioxidant NAC. Collectively, MIR1 plays an important role in C. albicans mitochondrial function, filamentation and virulence, and would be a promising antifungal target.